2018
DOI: 10.1038/s41556-018-0141-0
|View full text |Cite|
|
Sign up to set email alerts
|

IRE1α governs cytoskeleton remodelling and cell migration through a direct interaction with filamin A

Abstract: Maintenance of endoplasmic reticulum (ER) proteostasis is controlled by a signalling network known as the unfolded protein response (UPR). Here, we identified filamin A as a major binding partner of the ER stress transducer IRE1α. Filamin A is an actin crosslinking factor involved in cytoskeleton remodelling. We show that IRE1α controls actin cytoskeleton dynamics and affects cell migration upstream of filamin A. The regulation of cytoskeleton dynamics by IRE1α is independent of its canonical role as a UPR med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 59 publications
(76 reference statements)
6
94
0
Order By: Relevance
“…As illustrated in a model presented in Fig. 5G , we showed that Toxoplasma infection activates each of the UPR sensor proteins, including IRE1, via ER stress that results at least in part from release of calcium from the organelle, primarily through IP 3 R. In addition to its role in the UPR, IRE1 has recently been shown to have noncanonical functions associated with the remodeling of the cytoskeleton through direct interactions with the actin crosslinking factor filamin A [12]. We showed that Toxoplasma alters the morphology of its host cells through IRE1-filamin A interactions, which directs cytoskeletal remodeling that contributes to a hypermigratory phenotype that facilitated dissemination of the parasite into multiple organs of the infection host.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…As illustrated in a model presented in Fig. 5G , we showed that Toxoplasma infection activates each of the UPR sensor proteins, including IRE1, via ER stress that results at least in part from release of calcium from the organelle, primarily through IP 3 R. In addition to its role in the UPR, IRE1 has recently been shown to have noncanonical functions associated with the remodeling of the cytoskeleton through direct interactions with the actin crosslinking factor filamin A [12]. We showed that Toxoplasma alters the morphology of its host cells through IRE1-filamin A interactions, which directs cytoskeletal remodeling that contributes to a hypermigratory phenotype that facilitated dissemination of the parasite into multiple organs of the infection host.…”
Section: Discussionmentioning
confidence: 90%
“…Toxoplasma triggers rapid morphological changes in host cells, including disappearance of podosome structures and appearance of lamellipodia [20]. IRE1 has recently been shown to have noncanonical functions in actin cytoskeletal remodeling by directly binding to filamin A [12]. To address whether activation of IRE1 by Toxoplasma infection enhances host cell migration, we quantified the number of lamellipodia per infected cell normalized to uninfected cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations